Investigation of the GATA repetitive DNA sequence of the domestic horse (Equus caballus) of: a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University - Ede, Andrea J (Massey University, 1990)
The variation in copy number and organisation of the simple quadruplet repeat (GATA)n in the genome of most animals has made it a .potential tool for DNA fingerprinting. This study was undertaken to explore this application and to investigate its abundance and organisation in the horse genome. Using the synthetic oligomer (G ATA)5 end-labelled with 32P as a probe, the copy number of (GATA)n in genomic DNA from leukocytes of male and female horses was determined, and the extent of its polymorphism investigated on Southern blots of DNA digested with various restriction enzymes. To investigate its organisation, a genomic clone containing (GATA)n was isolated, characterized by restriction mapping and sequenced. (GATA)n constituted 1% of the horse genome. Like the mouse, there was no quantitative sex variation. Mbo I digestion generated a large number of horse DNA fragments of various sizes up to 5kb which hybridized to the (G AT A)5 probe. Simpler profiles were produced by digestion with Taq I, Alu I, Hae Ill and Hinf I. The profiles were highly conserved between individuals and between family members indicating the (G AT A)5 is unlikely to be informative as a DNA fingerprinting probe. Some intensely hybridizing DNA fragments appeared to be maternally transmitted. This seems to be a novel observation. A 3.6kb fragment which hybridized to the (G ATA)5 probe was cloned from horse genomic DNA. It was restriction mapped, the GATA-containing region identified and sequenced. Only about 150bp contained tandemly repeated GATA motifs in strings of about 3-6 repeats interspersed with (GAT)1-2 regions. The lack of quantitative sex variation suggests that (GATA)n may not have a role in sex determination in horses. Also, its lack of polymorphism makes it unlikely to be informative as a DNA fingerprinting probe.
Keywords: Horses; Genetics; DNA -- Analysis